Streamlining non‐governmental organizations' programs towards achieving the sustainable development goals: A conceptual framework - Hassan, M. M.; Lee, Khai Ern *; Mazlin, Mokhtar * (Wiley, 2019)
After the launching of sustainable development goals (SDGs), nongovernmental organizations (NGOs) are identified as prominent players in localizing the SDGs. This has drawn attention of the research communities to shift from single‐sector approach to cross‐sectors approach in achieving the SDGs. However, the different capacity of NGOs is defined by the gaps of institutional factors and different approaches contributing to uncertain impacts that cannot be measured persistently. This limitation has caused many NGOs to choose in maintaining single‐sector approach that has been practiced in the millennium development goals previously. Subsequently, this may result to the lack of SDGs output exchange from the NGOs. Therefore, this paper proposes a conceptual framework to streamline NGOs' programs towards achieving the SDGs in two mechanisms, namely, cross‐sectors partnerships and broadening social value. Cross‐sectors partnerships are developed crossing around the institutional sectors of society as one central partnering process to organize and respond to common issues and concerns in SDGs. Broadening social value is one form of NGO's mechanisms to raise a social interest crossing into many sectors in the role of shifting single‐sector approach to cross‐sectors approach. This conceptual framework provides a basis for NGOs to plan their programs based on their capability and capacity in achieving the SDGs' target.